Contemporary Endovascular Embolotherapy for Meningioma - Dubel, Gregory J.; Ahn, Sun Ho; Soares, Gregory M. (Seminars in Interventional Radiology, 2013)
Preoperative endovascular tumor embolization has been used for 40 years. Meningiomas are the most common benign intracranial tumor in which preoperative embolization has been most extensively described in the literature. Advocates of embolization report that it reduces operative blood-loss, and softens the tumor, thus making surgery safer and easier. Opponents suggest that it adds additional risk and cost for patients without controlled studies showing conclusive benefit. The literature suggests a 3 to 6% neurological complication rate related to embolization. The combined external and internal carotid artery blood supply and complex anastomoses of the meninges can make embolization challenging. Positive outcomes require thorough knowledge of the pertinent vascular anatomy, familiarity with the neurovascular equipment and embolics, and meticulous technique. There remains debate on several aspects of embolization, including tumors most appropriate for embolization, embolic agent of choice, ideal size of embolic, and the choice of vessel(s) to embolize. This detailed review of pertinent vascular anatomy, embolization technique, results, and complications should allow practitioners to maximize treatment outcomes in this setting.
Keywords: meningioma; embolization; complications; PVA; Gelfoam; interventional radiology